Предмет: Алгебра,
автор: tanyalg2345
![( - 3ab)^{4} ( - 3ab)^{4}](https://tex.z-dn.net/?f=%28+-+3ab%29%5E%7B4%7D++)
![( - 4ab)^{2} ( - 4ab)^{2}](https://tex.z-dn.net/?f=%28+-+4ab%29%5E%7B2%7D+)
![( - abc)^{5} ( - abc)^{5}](https://tex.z-dn.net/?f=%28+-+abc%29%5E%7B5%7D+)
![( - 2xyz)^{3} ( - 2xyz)^{3}](https://tex.z-dn.net/?f=%28+-+2xyz%29%5E%7B3%7D+)
помогите пожалуйста
Ответы
Автор ответа:
0
Ответ:
Объяснение:
(-3ab)⁴=(-3)⁴ab⁴=81ab⁴=
(-4ab)²=(-4)²a²b²=16a²b²
(-abc)⁵=-a⁵b⁵c⁵
(-2xyz)³=(-2)³x³y³z³=-8x³y³z³
tanyalg2345:
спасибо)
Похожие вопросы
Предмет: Английский язык,
автор: 12nikita98
Предмет: Английский язык,
автор: DragonGood
Предмет: Окружающий мир,
автор: Adelina18012005
Предмет: Математика,
автор: lasida42
Предмет: Литература,
автор: alesakeksik